2023
DOI: 10.1007/s10238-022-00987-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotics on gastrointestinal symptoms and microbiota in patients with celiac disease: a systematic review and meta-analysis on clinical trials

Abstract: ObjectivesGluten-free diet (GFD) is the most effective method to manage celiac disease (CD). Many patients do not reach the complete symptom alleviation, even by strict GFD. Recent studies have reported inconsistent results regarding the bene cial bene ts of taking probiotics. Therefore, we aimed to evaluate the effects of probiotics on gastrointestinal (GI) symptoms and the possible underlying causes in CD and celiac disease autoimmunity (CDA) patients. MethodsDatabases, including PubMed, Scopus, Embase, Web … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
10
0
2
Order By: Relevance
“…Reviews of studies indicate that probiotics may improve gastrointestinal symptoms in patients with CD, moderate the immune response, and improve dysbiosis in patients with CD and autoimmune CD. However, high-quality clinical trials are needed to increase the certainty of the evidence ( Seiler et al, 2020 ; Mozafarybazargany et al, 2023 ). The positive impact of probiotics on CD is primarily attributed to their ability to improve the tightness of the intestinal barrier.…”
Section: Celiac Disease Novel Therapiesmentioning
confidence: 99%
“…Reviews of studies indicate that probiotics may improve gastrointestinal symptoms in patients with CD, moderate the immune response, and improve dysbiosis in patients with CD and autoimmune CD. However, high-quality clinical trials are needed to increase the certainty of the evidence ( Seiler et al, 2020 ; Mozafarybazargany et al, 2023 ). The positive impact of probiotics on CD is primarily attributed to their ability to improve the tightness of the intestinal barrier.…”
Section: Celiac Disease Novel Therapiesmentioning
confidence: 99%
“…An agreement was reached among physicians and researchers about the role of probiotics in alleviating gastrointestinal symptoms, especially in symptomatic coeliac disease patients. This strategy is being tested by clinical trials instead of being enlisted as a remission strategy [ 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…The authors reported the quality of evidence was low for the effect of probiotics on overall gastrointestinal symptoms with a high risk of bias. Bifidobacteria levels were increased after the use of probiotics in two meta-analyses [ 158 , 162 ]. Another systematic review reported that a gluten-free diet in children with celiac disease supplemented by probiotic therapy can alter fecal microbiota to typical conditions of healthy individuals and reduce serum pro-inflammatory cytokines [ 163 ].…”
Section: Role Of Prebiotics and Probiotics For Various Gastrointestin...mentioning
confidence: 99%